2014
DOI: 10.3390/ma7128058
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Effects in Twin-Roll Cast AA8006 Aluminium Sheets Processed by Accumulative Roll-Bonding

Abstract: Ultrafine grained sheets were prepared from a twin-roll cast AA8006 aluminium alloy using accumulative roll-bonding process at room temperature. The evolution of microstructure of sheets after three accumulative roll-bonding passes during isochronal annealing with a constant step of 20 °C/20 min was studied by light and electron microscopy. The influence of the resulting microstructure on mechanical properties was monitored by microhardness measurements. The microhardness increases when the material is anneale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…The softening behaviour of the homogenized AA8006 sheet processed by 6 ARB cycles, i.e. the onset of recrystallization at 250°C is similar to the results reported for the same homogenized alloy in [20] after 3 and 5 ARB cycles. Birol [21] also reported that homogenized TRC Al-Fe-Mn sheet starts to recrystallize at much lower temperature (250 -280°C) than the supersaturated unhomogenized one (400 -450°C) [14].…”
Section: Thermal Stabilitysupporting
confidence: 83%
“…The softening behaviour of the homogenized AA8006 sheet processed by 6 ARB cycles, i.e. the onset of recrystallization at 250°C is similar to the results reported for the same homogenized alloy in [20] after 3 and 5 ARB cycles. Birol [21] also reported that homogenized TRC Al-Fe-Mn sheet starts to recrystallize at much lower temperature (250 -280°C) than the supersaturated unhomogenized one (400 -450°C) [14].…”
Section: Thermal Stabilitysupporting
confidence: 83%
“…Recently, techniques such as equal channel angular pressing [19,20], high-pressure torsion [21], accumulative roll bonding [22,23], repetitive corrugation and strengthening [24], and constrained groove pressing (CGP) [25] have been used to produce ultrafine-grained (UFG) materials. They were also successfully used to process high alloyed Al-Cu-Li materials [13,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Although TRC aluminium alloy sheets and foils are optimal candidates for further cold rolling reduction process, there is no available data on an influence of CRR rates on TRC 8006 aluminium alloy's corrosion properties. Also, corrosion characteristics of various aluminium alloys produced by TRC resulting surface roughness profiles has been subjected to attention for the past decades because of its importance in pitting corrosion resistance [2,6,13,15]. The present work is aimed to study the effect of cold rolling reduction rate as that achieved during the twin-roll casting process, on corrosion behaviour of 8006 aluminium alloys in 1M NaCI aqueous solution environment.…”
Section: Introductionmentioning
confidence: 99%
“…8006 aluminium alloys are widely used for manufacturing the packaging foils and sheets for common heat exchanger applications [13,14]. Increasing demands of the industry on corrosion resistance, mechanical properties and formability has evoked an intensive investigation of sheets and foils with an influence of cold rolling reduction rate [15][16][17]. Although TRC aluminium alloy sheets and foils are optimal candidates for further cold rolling reduction process, there is no available data on an influence of CRR rates on TRC 8006 aluminium alloy's corrosion properties.…”
Section: Introductionmentioning
confidence: 99%